Protocol of a randomised controlled phase II clinical trial investigating PREoperative endoscopic injection of BOTulinum toxin into the sphincter of Oddi to reduce postoperative pancreatic fistula after distal pancreatectomy: the PREBOTPilot trial - Klaiber, Ulla; Sauer, Peter; Martin, Eike; Bruckner, Thomas; Luntz, Steffen P.; Tjaden, Christin; Probst, Pascal; Knebel, Phillip; Diener, Markus K.; Büchler, Markus W.; Hackert, Thilo (BMJ open, 2020)
Introduction Postoperative pancreatic fistula (POPF) is still the most frequently occurring and clinically relevant complication after distal pancreatectomy (DP). Preoperative endoscopic injection of botulinum toxin (BTX) into the sphincter of Oddi represents an innovative approach to prevent POPF. The aim of this project (PREBOTPilot) is to generate the first randomised controlled trial data on the safety, feasibility and efficacy of preoperative endoscopic BTX injection into the sphincter of Oddi to prevent clinically relevant POPF following DP. - Methods and analysis PREBOTPilot is an investigator-initiated, single-centre, randomised, controlled, open-label, phase II clinical trial with two parallel study groups and an exploratory study design. 60 patients scheduled for DP will be randomised to intervention and control group. In the intervention group, patients will undergo preoperative endoscopic injection of BTX into the sphincter of Oddi, whereas in the control group no preoperative endoscopy will be performed. The combined primary endpoint is the occurrence of clinically relevant POPF and/or death within 30 days after DP. The secondary endpoints comprise further postoperative outcome parameters and quality of life up to 3 months after DP as well as safety and feasibility of the procedure. Statistical analysis is based on the modified intention-to-treat population, excluding patients without status post DP. For safety analysis, rates of adverse events (AEs) and serious AEs will be calculated with 95% CIs for group comparisons. - Ethics, funding and dissemination PREBOTPilot has been approved by the German Federal Institute for Drugs and Medical Devices (reference number 4043654) and the Ethics Committee of Heidelberg University (reference number AFmo-523/2019). This trial is supported by the German Federal Ministry of Education and Research (BMBF). The results of the trial will be presented at national and international conferences and published in a peer-reviewed journal. - Trial registration number DRKS00020401.
Gesehen am 13.10.2020